The relationship between psychosocial predictors and employee readiness to change - Mardhatillah, Amy Mardhatillah; Abdul Rahman, Shukran; Ismail, Khamsiah (University Putra Malaysia, 2017)
Seventy percent of organizations experience failure in implementing organizational change (Miller & Peter, 2006). One of the reasons for this failure is the lack of careful assessment of an organization’s readiness to change, which depends much on the employees’ readiness to change. This study investigates predictors of employees’ readiness to change, namely, appropriateness of change, management support, change efficacy, individual spirituality, and openness to experience. The present study also examined the role of job satisfaction and organizational commitment in mediating between psychosocial predictors and employee readiness to change. A random sampling (n = 428) of a Higher Learning Institution in Malaysia consisting 214 academic staff and 214 non–academic staff participated in this study. Two–step Structural Equation Modelling was used to answer the research questions. Results of the measurement model indicated that all measurements used are valid. The structural model in the present study indicated that psychosocial factors including appropriateness, management support, change efficacy, individual spirituality, and openness to experience significantly predict employee readiness to change. Result shows that appropriateness of change, management support, change efficacy, and openness to experience are indirectly related with employee readiness to change via a mediating role of organizational commitment. This result indicated that employees who perceived the change to be appropriate show openness toward change and that perceived management support will not enhance their readiness to change unless they are committed to the organization. In addition, individual spirituality and change efficacy are directly related with employee readiness to change.